Distributed computing in the modern enterprise. - Feldman, Stuart (New York ACM, 2005)
Grids, SOAs, web services, and beyond
Keywords: General Literature; Miscellaneous; Computer Systems Organization; Computer Communication Networks; Network Architecture and Design; Distributed networks; Distributed systems; Distributed applications; Information Systems; Information Storage and Retrieval; Systems and Software; On-line information systems; Web based services